HOPCA - Cemre Çubukçuoğlu (A+BE: Architecture and the Built Environment)
Hospitals are known as functionally complex buildings in various ways, namely due to their non-trivial spatial connectivity requirements. A spatial configuration has an impact on human behavior, human movement patterns and should match with the operational logic of the buildings. In hospitals, there are several typical problems that can be attributed to the configuration of the building, namely the inefficient circulation of medical staff, difficult way-finding for visitors, lengthy and complex procedures for patients, long walking times, privacy, hygiene issues and so on.